Okonkwo's Internal Conflicts in Chinua Achebe's Things Fall Apart: A Psychological Analysis - Subekti, Adaninggar Septi; Novianti, Maria Niayu Risma; Wahyuni, Aprilia Kristiana Tri (TELL - US JOURNAL, 2020)
This study discussed internal conflicts experienced by Okonkwo, the main character, in Chinua Achebe’s Things Fall Apart. The novel tells about Okonkwo’s life in Umuofia. He struggled to make a prosperous and dignified life, unlike his disgraceful late father, Unoka, and valued the Umuofia tradition and culture very highly. He grew up to be a strong man in his neighbourhood.  However, despite his strength and bravery, the biggest fear in his life was to fall and become weak resembling his father. Based on the main character’s experiences and environments, a psychological analysis was used to find out how someone’s experiences had shaped his way of thinking even his actions to make a decision. Therefore, this study focused on internal conflicts as a part of the psychological approach. The conflicts that examined were approach-avoidance and avoidance-avoidance conflicts where the decisions taken by Okonkwo could have both risks and opportunities (approach-avoidance) or only risks (avoidance-avoidance). To solve his internal conflicts, the main character should choose which decision that would give more opportunities or fewer risks.